Desain Konseptual Internet Accelerator Laboratory (IAL) untuk Siklotron DECY-13 - Frida Iswinning Diah; Idrus Abdul Kudus; Suharni; Fajar Sidik Permana; Taxwim (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2022)
Research and Technology Center for Accelerator of Research Organization for Nuclear Energy of National Research and Innovation Agency (PRTA-ORTN – BRIN) has become the Center for Excellence in Science and Technology (PUI), especially in the particle accelerator field. One of the studies is the DECY-13 cyclotron for radioisotopes production used in the medical field for cancer diagnostics. Currently, the DECY-13 cyclotron R&D is in the final stages of the design process. A Cyclotron internet laboratory facility will be implemented to expand the benefits of this R&D. This facility will support the cyclotron training to be more widely accessible and increase capacity building and human resources programs in the nuclear field. Therefore, a preliminary study for DECY-13 cyclotron Internet Accelerator Laboratory (IAL) is needed, which includes the preparation of long-term concepts and the design of IAL. The formulation of the long-term idea follows the established cyclotron road map. In the conceptual design, the users at the early stages are students and cyclotron operators in hospitals. In order to determine the design requirement, the next step is a literature study on online laboratories and the accelerator learning concept that has been applied in other countries. The IAL apparatus identification is based on a review of the DECY-13 cyclotron laboratory's current conditions and future research plans. The conceptual design that has been successfully developed consists of a research roadmap on IAL for long-term research planning and a material syllabus for two target users, namely students and cyclotron operators in hospitals. While the employed IAL component identification is CompactRIO as the primary controller on the cyclotron operating system and as a liaison with the network system. Supporting the network includes database systems, servers, LAN, internet, webcams, and websites or an application to be accessed by users.